Developing Practices in Multicultural Society - Rosita Tandos (UIN Siber Syekh Nurjati Cirebon, 2017)
Globalization has brought people and cultures closed one another that affect the aspects of life. It has impact in shaping a multicultural society that consists of various ethnicity, race, class, and gender. Then, multiculturalism has been considered significantly in addressing issues experienced mainly by ethnicities and religious groups. Moreover, it play an important role in the current global condition in which the world recently becoming closer and inter-dependence.Therefore, community workers or any helping profession need to work for managing diversity, not just sufficiently celebrating and acknowledging it. Furthermore, social interventions and services at any aspects of life (social, cultural, education, economic and political) should also integrate the notion of diversities and pluralism, shaping the life of multicultural society.This paper aims to introduce the need for understanding and developing localities multiculturalism as a process that is always contextual, affecting significantly on community organizing and education programs. In discussing the main topic, this paper also focuses on three main frameworks: Islamic perspective and community development theories. These frameworks are used to figure out the challenges or issues existing in the life of communities, with identifying resources and developing a logical framework for community organizing and development as one of interventions to change system and policy.The paper covers two main points of multicultural society and developing practice in multicultural society. The last point specifically focus on the ideas of localities, mentioned by Ife (2002) and apply it in community work or practice. The discussion of this paper include the questions that want to be answered, followed by the discussion of the two main points, while the last session is conclusion that provides some recommendations for changing policy, improving program and services.Â Key words: multiculturalism, Islamic perspective, and community development